2019
DOI: 10.18332/tpc/114085
|View full text |Cite
|
Sign up to set email alerts
|

The association between smokers’ self-reported health problems and quitting: Findings from the ITC Four Country Smoking and Vaping Wave 1 Survey

Abstract: INTRODUCTION This study aimed to systematically examine whether having health conditions or concerns related to smoking are associated with quitting activities among smokers across four western countries. METHODS Data came from the 2016 International Tobacco Control Four Country Smoking and Vaping Survey conducted in Australia, Canada, England and US. We asked smokers and recent quitters (n=11838) whether they had a medical diagnosis for heart disease, cancer, chronic lung disease, depression, anxiety, alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The results show that believing smoking had harmed/would harm their health and reported specific health conditions, except for alcohol problems, were positively associated with quit attempts. However, associations between health conditions and planning to quit in the future and use of quitting medications were less consistent 9 . These cross-sectional findings need to be tested longitudinally to see if the same associations apply.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The results show that believing smoking had harmed/would harm their health and reported specific health conditions, except for alcohol problems, were positively associated with quit attempts. However, associations between health conditions and planning to quit in the future and use of quitting medications were less consistent 9 . These cross-sectional findings need to be tested longitudinally to see if the same associations apply.…”
Section: Introductionmentioning
confidence: 89%
“…Research shows that quitting rates remain low among many patients with COPD and other chronic conditions, despite being aware of the specific link between their condition and smoking 5 . An earlier cross-sectional study 9 showed that levels of use of the strongest possible cessation help was disappointingly low. Coupled with our new findings, it suggests a pressing need to find better ways to support smokers with smoking-related conditions to use the strongest possible tools to maximize their capacity to quit successfully.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was based on a community setting where participants were healthy. However, evidence reported successful smoking cessation intervention in unhealthy volunteers (Samaan et al, 2012;Pires-Yfantouda et al, 2013;Guilleminault et al, 2018) and observational study shows the association between unhealthy status and quit smoking (Li et al, 2019). We observed the significance of the number of cigarettes smoked per day.…”
Section: Discussionmentioning
confidence: 44%